Fieldwork in geography education: an experience in initial teacher training program - Esteves, Maria Helena (2019)
Fieldwork in geography education is an important activity in terms of promoting the development of geographical knowledge and skills that go beyond school learning. The way this contact with the real world is done has evolved from the traditional school visit (fieldtrip) to models where students’ involvement is deeper representing the contribution of several educational theories in geography educational practices. This paper presents a rational about fieldwork implementation as a methodology of data collection used in research undertaken at a local scale, included in a program of geography initial teacher training. As the experience took place in an urban area, the paper includes a conceptual framework about the potential of the city as a research area in terms of fostering critical thinking and the formation of geographically competent citizens.